REMOTE DEFECTOSCOPY OF INTERNAL SURFACES OF TUBES - D. A. Gorbunov; P. I. Markov; L. P. Maljavko (Литьë и металлургия)
Remote scanning of internal cavities broadens the fields of practical application of optical defectoscopy and diagnostics of state of expanded articles of variable cross-sections with automatic optical system control and optoelectronic processing of video picture.